La zona minera de La Bessa (Italia): sectores de explotación y evaluación de las labores - F. Javier Sánchez-Palencia; Alberto Vaudagna; Juan Luis Pecharromán; Eneko Iriarte (Mélanges de la Casa de Velázquez, 2018)
The La Bessa mining area (Biella, Piamonte, Italy) was worked during the Republican period (2nd–1st centuries BCE) to extract gold from a fluvio-glacial deposit. The system of exploitation used is rather hard to interpret given that it was pursued exhaustively in small parcels. In the final analysis, it was based on the use of water power throughout the mining process, and as such is a significant precedent to the large-scale gold mining in secondary deposits in Hispania. The interpretation of these exploitation systems has been updated through the integration of photo interpretation and geographic information techniques. Particularly important in that interpretation has been the identification of the structures of removal and stockpiling of excavated material, which has made it possible to assess all the material removed.